Quality of life and labor inclusion of people with disabilities - Lerma Castaño, Piedad Rocío; Tamayo Perdomo, Gladys; Wees Verhelst, Yolima; Alvarado Rozo, Ómar Alberto (Revista Médica de Risaralda, 2023)
Introduction: Disability is a generic term that includes deficits, limitations in activity and restrictions in participation indicate the negative aspects of the interaction between an individual and its contextual factors, environmental and personal factors. Objective: The objective of this study was to identify the characteristics of labor inclusion and health-related quality of life of people with disabilities in a population group from the city of Neiva (Colombia). Materials and methods: Descriptive, analytical, cross-sectional study with quantitative approach and non-experimental design, in a sample of 64 people with disabilities. Demographic variables such as age, sex, marital status, education, socioeconomic status, link to the social security system in health, and type of disability were considered. The WHOQOL-BREF, 2004 quality of life scale was applied. Central tendency measures were also calculated with their dispersions and 95% confidence intervals in the continuous quantitative variables. Results: The most frequent disability was physical with 78.13%, followed by visual with 17.18%. The highest percentage of impairment of the quality of life concerning disability is given by the need to move from one place to another, to feel dissatisfaction with their sexual life and the perception of an unhealthy environment. Conclusions: The main factors for the labor inclusion of a person with a disability are subject to sex, the type of disability, access to decent employment, and remuneration according to their potentialities.